Postoperative infection and mortality following elective surgery in the International Surgical Outcomes Study (ISOS). Issue 2 (18th January 2021) - Wan, Y I; Patel, Akshaykumar; Achary, C; Hewson, R; Phull, M; Pearse, R M; ,
Abstract: Background: Postoperative infection is one of the most frequent and important complications after surgery. The epidemiology of infection following elective surgery remains poorly described. Methods: This was a prospective analysis of the International Surgical Outcomes Study (ISOS) describing infection by 30 days after elective surgery. Associations between postoperative infection (primary outcome) and baseline demographic, surgical, and anaesthetic risk factors were assessed. Analyses were carried out using logistic and linear regression models. Secondary outcomes were 30-day mortality and duration of hospital stay. Treatments received by patients after different types of infection were evaluated. Results: Some 44 814 patients were included in the analysis, with a total of 4032 infections occurring in 2927 patients (6.5 per cent). Overall, 206 patients died, of whom 99 of 2927 (3.4 per cent) had infection. Some 737 of 4032 infections (18.3 per cent) were severe; the most frequent types were superficial surgical-site infection (1320, 32.7 per cent), pneumonia (708, 17.6 per cent), and urinary tract infection (681, 16.9 per cent). Excluding missing data, antimicrobials were used in 2126 of 2749 infections (77.3 per cent), and 522 of 2164 patients (24.1 per cent) required admission to critical care. Factors associated with an increased incidence of infection in adjusted analyses were: age, male sex, ASA grade, co-morbid disease, preoperative anaemia, anaesthetic technique, surgical category, surgical severity, and cancer surgery. Infection significantly increased the risk of death (odds ratio 4.68, 95 per cent c.i. 3.39 to 6.47; P < 0.001), and duration of hospital stay by on average 6.45 (6.23 to 6.66) days ( P < 0.001). Conclusion: Infection is a common complication after elective surgery. Recognition of modifiable risk factors will help inform appropriate prevention strategies. Abstract : Infection occurred in one in 15 patients undergoing elective surgery. Patients with infection were 4.68 times more likely to die. Prevention strategies are increasingly important given the growing problem of antimicrobial resistance. Infections common after elective surgery.